BacaMAX: Addressing visual deficit to facilitate reading for dyslexic children - Husni, Husniza; Jamaludin, Zulikha (Asian Research Publishing Network (ARPN), 2015)
This paper proposes BacaMAX, an educational technology application to ease reading and text processing for dyslexic children.Being diagnosed as dyslexics, children (adults too) are facing greater challenge to learn to read.One of the main theories of dyslexia is due to visual impairment, which is not referring to the problems with the eyes but with the information processing that took place inside the brain.Apparently, those who are facing this problem trigger the wrong part of the brain to process text thus creating difficulties in reading.Aiming to reduce this issue, a specific design is proposed mainly for interactive applications to support reading for dyslexics.The design is tailored to meet the dyslexic children’s requirement and need, taking into account the three dimensions of Interaction Design (IxD) and minimalist concept.To prove the concept, a high fidelity prototype, called BacaMAX, has been developed.The prototype was developed using the six steps of Goal Directed Design (GDD) method.Currently, BacaMAX is being tested in a primary school that runs special dyslexia classes.The application’s effect to children’s interest and learning experience has been positive.